2019
DOI: 10.3389/fphar.2019.01040
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate Improves the Metabolic Disorder and Gut Microbiome Dysbiosis in Mice Induced by a High-Fat Diet

Abstract: Background: Metabolic syndrome (MS) is one of the major causes of coronary artery diseases (CAD). Gut microbiome diversity and its natural fermentation products are not only correlated with MS and CAD, but their correlations also appear to be stronger than the associations with traditional risk factors. Therefore, the aim of this study was to provide a new potential pathway for the natural fermentation product butyrate to improve MS and to examine whether it is associated with serum metabolic profiles and gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 31 publications
(34 reference statements)
1
44
0
Order By: Relevance
“…Previous study reported that fucoidan from Laminaria japonica significantly increased the relative abundance of Ruminococcaceae while the abundance of Verrucomicrobia decreased, which is consistent with our current results [69]. Ruminococcaceae and Lachnospiraceae are predominant families of intestinal bacteria involved in carbohydrate metabolisms [70,71]. Many SCFA-producing bacteria also belong to these families.…”
Section: Discussionsupporting
confidence: 92%
“…Previous study reported that fucoidan from Laminaria japonica significantly increased the relative abundance of Ruminococcaceae while the abundance of Verrucomicrobia decreased, which is consistent with our current results [69]. Ruminococcaceae and Lachnospiraceae are predominant families of intestinal bacteria involved in carbohydrate metabolisms [70,71]. Many SCFA-producing bacteria also belong to these families.…”
Section: Discussionsupporting
confidence: 92%
“…Several mechanisms may explain the changes in hepatic lipid content. The butyrate produced in intestinal lumen, which is an energy source for colonocytes, can activate the AMPK signalling pathway in intestinal epithelium, inhibiting hepatic cholesterol and fatty acids synthesis (Gao et al., 2019; Rumberger, Arch, & Green, 2014; Song et al., 2019). In our study, a combined wheat bran fibre and inulin diet feeding tended to reduce the butyrate concentrations in colon, which may lead to a reduced inhibition of hepatic lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In rats on a high-fat diet, butyrate supplementation induced the activation of AMP-activated 5 Protein Kinase (AMPK) and glucose transporter 4 (GLUT4) in the adipose tissue, attenuated diet-induced dysbiosis, promoted biosynthesis of resolvin E1 and lipoxin (anti-inflammatory lipid mediators) [175], attenuated weight gain, adiposity, adipocyte hypertrophy, inflammation, and leptin secretion [176]. In the same animal model, butyrate supplementation appears to induce lipolysis in WAT mediated by activation of β3-adrenergic receptors [177] and regulates gene expression related to intestinal cholesterol absorption resulting in attenuation of atherosclerosis [178].…”
Section: Butyratementioning
confidence: 99%